Faktor-Faktor yang Mempengaruhi Kelengkapan Imunisasi Dasar pada Bayi di Desa Ujung Labuhan Kecamatan Namorambe Kabupaten Deli Serdang Tahun 2025: Penelitian - Mastiur Julianti B; Indah Yani Tambunan; Esther Siringo-Ringo (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study was to determine the factors that influence the completeness of basic immunization in infants in Ujung Labuhan Village, Namorambe District, Deli Serdang Regency in 2025. The type of research used is observational analytic with a cross-sectional approach;.  Based on the results of research on the factors that influence the completeness of basic immunization in infants in Ujung Labuhan Village, Namorambe District, Deli Serdang Regency in 2025, it can be concluded as follows: There is no effect of knowledge on the completeness of basic immunization in infants in Ujung Labuhan Village, Namorambe District, Deli Serdang Regency in 2025, with a p-value of 0.334> 0.05. There is no effect on the attitude of basic immunization in infants in Ujung Labuhan Village, Namorambe District, Deli Serdang Regency Deli Serdang in 2025, with a p-value of 0.177>0.05. There is an influence of motivation on the completeness of basic immunization in infants in Ujung Labuhan Village, Namorambe District, Deli Serdang Regency in 2025, with a p-value of 0.032<0.05. There is no influence of work on the completeness of basic immunization in infants in Ujung Labuhan Village, Namorambe District, Deli Serdang Regency in 2025, with a p-value of 0.206>0.05.